Genotoxicity and cytotoxicity potential of organoselenium compounds in human leukocytes in vitro - Mohammad Ibrahim; Daiane Francine Meinerz; Momin Khan; Abid Ali; Muhammad Idrees Khan; Abdullah F. AlAsmari; Metab Alharbi; Abdulrahman Alshammari; João Batista T. da Rocha; Fawaz Alasmari (Elsevier, 2023)
In the current work, cytotoxicity and genotoxicity of different organoselenium compounds were examined using Trypan blue exclusion and alkaline comet assays with silver staining respectively. Leukocytes were subjected to a 3-hour incubation with organoselenium compounds at concentrations of 1, 5, 10, 25, 50, and 75 μM, or with the control vehicle (DMSO), at a temperature of 37 °C. The viability of the cells was evaluated using the Trypan blue exclusion method, while DNA damage was analyzed through the alkaline comet assay with silver staining. The exposure of leukocytes to different organoselenium compounds including i.e. (Z)-N-(pyridin-2-ylmethylene)-1-(2-((2-(1-((E)-pyridin-2-ylmethyleneamino)ethyl)phenyl)diselanyl)phenyl)ethanamine (C1), 2,2'(1Z,1'E)-(1,1'-(2,2'-diselanediylbis(2,1-phenylene))bis(ethane-1,1-diyl)) bis(azan-1-yl-1-ylidene)bis -methan-1-yl-1-ylidene)diphenol (C2), and dinaphthyl diselenide (NapSe)2, At concentrations ranging from 1 to 5 μM, no significant DNA damage was observed, as indicated by the absence of a noteworthy increase in the Damage Index (DI).Our results suggest that the organoselenium selenium compounds tested were not genotoxic and cytotoxic to human leukocytes in vitro at lower concentration. This study offers further insights into the genotoxicity profile of these organochalcogens in human leukocytes. Their genotoxicity and cytotoxicity effects at higher concentration are probably mediated through reactive oxygen species generation and their ability to catalyze thiol oxidation.